Convergence of the Collatz Sequence - Nikolaychuk, Anatoliy (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
For any natural number was created the supplement sequence, that is convergent together with the original Collatz sequence. The numerical parameter - index was defined, that is the same for both sequences. This new method provides the following results: All natural numbers were distributed into six different classes; The properties of index were found for the different classes; For any natural number was constructed the bounded sequence of increasing numbers, that is convergent together with the regular Collatz sequence.